Which Indicators are Suitable to Measure ESD Implementation in Formal Education? Results of an Expert Consultation from Academia and Education Administration - Hemmer, Ingrid; Winter, Marc; Mainka, Steven; Ullrich, Mark; Bagoly-Simó, Péter; Lude, Armin; Labanino, Rafael (Journal of Geography Education, 2023)
What are the ways to measure the implementation of Education for Sustainable Development (ESD) in school education? This paper reports on a questionnaire-based expert consultation carried out within a larger research project following two main objectives, namely how expert participants assessed the individual indicators of a proposed set of indicators and whether there were differences between the two expert groups (academia, education administration). The results showed that both expert groups viewed curricula, training, school labels, school management training, and ESD strategy as the most important areas. Their assessment did not differ significantly.